The strategic marketing planning – General Framework for Customer Segmentation - OPRESCU, Alina Elena (Annals of Spiru Haret University. Economic Series, 2014)
Any approach that involves the use of strategic resources of an organisation requires a responsible approach, a behaviour that enables it to properly integrate itself into the dynamic of the business environment. This articles addresses in a synthetic manner, the issues of specific integration efforts for customers’ segmentation in the strategic marketing planning. The essential activity for any organisation wishing to optimise its response to the market, the customer segmentation will fully benefit from the framework provided by the strategic marketing planning. Being a sequential process, it not only allows time optimisation of the entire marketing activity but it also leads to accuracy of the strategic planning and its stages.